Development and evaluation of the CoBo application: enhance confidence and social skills through physical education for bullying victims - Firmana, Iif; Wahidi, Ribut; Sofyan, Davi (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Bullying remains a persistent issue in physical education (PE), often leading to decreased student participation, low self-confidence, and poor social interaction. While several anti-bullying interventions exist, few are tailored specifically to the PE context or leverage technology to promote engagement and resilience. This gap underscores the need for innovative, context-specific tools such as the CoBo application. Objectives: This study explores the design, development, implementation, and evaluation of the CoBo application—an interactive educational tool aimed at enhancing confidence, social skills, and participation in physical activities among primary school pupils. Methods: A research and development (R&D) approach was adopted, beginning with a needs analysis through interviews with PE teachers, students, and bullying victims. Finding/Results: Findings revealed a strong need for an engaging, supportive digital resource to help students cope with bullying and re-engage in PE. In response, CoBo was developed with modules targeting self-confidence, social competence, anti-bullying strategies, physical activities, and motivation. Prototype and pilot testing involving bullied students demonstrated improved self-efficacy, socialization, and PE participation. Conclusion: CoBo offers a promising technology-based solution for addressing bullying in PE settings. Future research should expand testing across diverse school populations to assess broader applicability and long-term impact.